Country perspective on medical tourism: the Malaysian experience - Abd. Manaf, Noor Hazilah; Hussin, Husnayati; Jahn Kassim, Puteri Nemie; Alavi, Rokiah; Dahari, Zainurin (Emerald, 2015)
Purpose – The study seeks to explore the perception of international patients on Malaysia as a medical tourism destination country, as well as overall patient satisfaction, perceived value and future intention for repeat treatment and services. Design/methodology/approach – Self-administeredquestionnairewasthemainmethodofdatacollection. The survey covered major private hospitals in medical tourists’ states in the country, namely, Penang, Melaka, Selangor and Kuala Lumpur. Convenience sampling was used due to the condition of patients as respondents. Findings – Indonesian patients formed the largest majority of international patients in the country. Five dimensions of medical tourism in Malaysia was identified, namely, hospital and staff, country factor, combining tourism and health services, cost saving and insurance and unavailability of treatment. Of these, hospital and staff was found to be the most important factor for the patients. Perception of value, overall satisfaction and intention for future treatment was also found to be high. This indicates that Malaysia is on the right footing in this burgeoning industry. Practical implications – Findings from the study will enable policy-makers to better position Malaysia as a medical tourist destination country. Originality/value – Medical tourism is a recent phenomenon and very little empirical research has been carried out at the patient level. This study is one of the first few studies which seek to explore medical tourism from the perspective of the patients themselves.